Preoperative 4D CT Localization of Nonlocalizing Parathyroid Adenomas by Ultrasound and SPECT‐CT. (6th August 2015) - Hinson, Andrew M.; Lee, David R.; Hobbs, Bradley A.; Fitzgerald, Ryan T.; Bodenner, Donald L.; Stack, Brendan C.
Abstract : Objective: To evaluate 4‐dimensional (4D) computed tomography (CT) for the localization of parathyroid adenomas previously considered nonlocalizing on ultrasound and single‐photon emission CT with CT scanning (SPECT‐CT). To measure radiation exposure associated with 4D‐CT and compared it with SPECT‐CT. Study Design: Case series with chart review. Setting: University tertiary hospital. Subjects and Methods: Nineteen adults with primary hyperparathyroidism who underwent preoperative 4D CT from November 2013 through July 2014 after nonlocalizing preoperative ultrasound and technetium‐99m SPECT‐CT scans. Sensitivity, specificity, predictive values, and accuracy of 4D CT were evaluated. Results: Nineteen patients (16 women and 3 men) were included with a mean age of 66 years (range, 39‐80 years). Mean preoperative parathyroid hormone level was 108.5 pg/mL (range, 59.3‐220.9 pg/mL), and mean weight of the excised gland was 350 mg (range, 83‐797 mg). 4D CT sensitivity and specificity for localization to the patient's correct side of the neck were 84.2% and 81.8%, respectively; accuracy was 82.9%. The sensitivity for localizing adenomas to the correct quadrant was 76.5% and 91.5%, respectively; accuracy was 88.2%. 4D CT radiation exposure was significantly less than the radiation associated with SPECT‐CT (13.8 vs 18.4 mSv, P = 0.04). Conclusion: 4D CT localizes parathyroid adenomas with relatively high sensitivity and specificity and allows for the localization of some adenomas not observed on other sestamibi‐based scans. 4D CT was also associated with less radiation exposure when compared with SPECT‐CT based on our study protocol. 4D CT may be considered as first‐ or second‐line imaging for localizing parathyroid adenomas in the setting of primary hyperparathyroidism.